Physical activity and sedentary behaviour interventions for people living with both frailty and multiple long-term conditions: a scoping review protocol. Issue 5 (4th May 2022) - Young, Hannah M L; Yates, Thomas; Dempsey, Paddy C; Herring, Louisa Y; Henson, Joseph; Sargeant, Jack; Curtis, Ffion; Sathanapally, Harini; Highton, Patrick J; Hadjiconstantinou, Michelle; Pritchard, Rebecca; Lock, Selina; et al.
Abstract : Introduction: The number of people living with multiple long-term conditions (MLTCs) is predicted to rise. Within this population, those also living with frailty are particularly vulnerable to poor outcomes, including decreased function. Increased physical activity, including exercise, has the potential to improve function in those living with both MLTCs and frailty but, to date, the focus has remained on older people and may not reflect outcomes for the growing number of younger people living with MLTCs and frailty. For those with higher burdens of frailty and MLTCs, physical activity may be challenging. Tailoring physical activity in response to symptoms and periods of ill-health, involving family and reducing sedentary behaviour may be important in this population. How the tailoring of interventions has been approached within existing studies is currently unclear. This scoping review aims to map the available evidence regarding these interventions in people living with both frailty and MLTCs. Methods and analysis: We will use a six-stage process: (1) identifying the research questions; (2) identifying relevant studies (via database searches); (3) selecting studies; (4) charting the data; (5) collating and summarising and (6) stakeholder consultation. Studies will be critically appraised using the Mixed Methods Appraisal Tool. Ethics and dissemination: All data in this project will be gathered through database searches. Stakeholder consultation will be undertaken with an established patient and public involvement group. We will disseminate our findings via social media, publication and engagement meetings.